Opportunities to engage health system leaders in whole systems approaches to physical activity in England - E. L. Bird; D. Evans; S. Gray; E. Atherton; J. Blackshaw; M. Brannan; N. Corrigan; D. Weiner (BMC, 2022)
Abstract Background Physical activity plays an important role in maintaining good health and wellbeing, non-communicable disease prevention and can improve healthcare outcomes. Some progress is being made on incorporating physical activity into routine care, but less on engaging health system leaders in the 'whole systems' approaches which are increasingly recognised as important for addressing complex public health challenges such as physical inactivity. This commentary builds upon the findings of a recent study and aims to identify opportunities for engaging National Health Service (NHS) systems leaders in whole systems approaches to physical activity. Opportunities for action in England Pockets of good practice exist from which lessons can be learned, but there are systemic issues that discourage and create barriers, and a need for meaningful engagement, leadership and action at national, regional and local levels. National and regional actors like Sport England, NHS England, health professional bodies, Active Partnerships, the Local Government Association and the Office for Health Improvement and Disparities can encourage and support government and the NHS to change policy drivers, culture and practices. Emerging opportunities include the 2021 White Paper Integration and Innovation, development of local integrated care systems, leadership from health charities and investment in non-clinical interventions ('social prescribing'). At local level, public health and physical activity specialists and other organisations have a key role as champions and facilitators of local whole systems approaches and engagement of local NHS leaderships. Finally, although whole systems action is about collaborative leadership, individual champions of physical activity can make a difference in influencing NHS leaders at every level towards whole systems working.